2015
DOI: 10.1007/s40430-015-0388-3
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration analysis of sigmoid functionally graded nanobeams based on a modified couple stress theory with general shear deformation theory

Abstract: Free vibration of nano-scale beams made of sigmoid functionally graded material is studied based on the modified couple stress theory. In the context of the modified couple stress theory, a material length scale parameter is used to describe the size effect. The classical, first-order and some higher order beam theories are considered to assess the effect of shear deformation. Differential equations of motion and boundary conditions are derived using Hamilton's principle. The equations of motion are discretize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Figure 6 illustrates the effect of number of nodes and the smoothing length value on the convergence of deflection response of a simply supported two-directional FG nanobeam with the following properties: k x = k z = 2, = 1 nm 2 , E ratio = 2. Numerical calculations are performed using uniformly distributed 9,15,17,19,21,23,25,27,41,81 and 121 nodes in the problem domain for three different values of smoothing length. According to the obtained results, the convergence rate is faster for h 0 = 1.2Δ.…”
Section: Results For Bending Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 illustrates the effect of number of nodes and the smoothing length value on the convergence of deflection response of a simply supported two-directional FG nanobeam with the following properties: k x = k z = 2, = 1 nm 2 , E ratio = 2. Numerical calculations are performed using uniformly distributed 9,15,17,19,21,23,25,27,41,81 and 121 nodes in the problem domain for three different values of smoothing length. According to the obtained results, the convergence rate is faster for h 0 = 1.2Δ.…”
Section: Results For Bending Analysismentioning
confidence: 99%
“…In a recent paper by Ebrahimi and Barati, analytical solutions were obtained for free vibration of FG nanobeams based on the Reddy-Bickford beam theory [31]. Further studies addressing the behavior of ordinary and FG nanobeams can be found in [32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many investigations have been conducted to compute the Casimir attraction for different geometries including parallel plates [16][17][18], plate-sphere [19], parallel cylinders [20] and plate-cylinder [21]. Several investigations have investigated the instability characteristics and nonlinear analysis of micro/nano-scale structures by employing different assumptions and theories such as nonlocal elasticity [22][23][24] modified couple stress theory [25][26][27][28], strain gradient theory [29,30], modified strain gradient theory [31], strain-inertia gradient elasticity [32], etc. A nano-scale device might adhere to its substrate due to Casimir force if the minimum gap between the flexible beam and the substrate is not considered.…”
mentioning
confidence: 99%